Modulating the deep-level defects and charge extraction for efficient perovskite solar cells with high fill factor over 86%. Issue 11 (17th October 2022) - Li, Xingcheng; Wu, Xin; Li, Bo; Cen, Zeyan; Shang, Yanbo; Lian, Weitao; Cao, Rui; Jia, Lingbo; Li, Zhen; Gao, Danpeng; Jiang, Xiaofen; Chen, Tao; et al.
Abstract : An effective way has been developed to realize high-performance perovskite solar cells. The relationship between deep-level defects, carrier mobility, charge extraction efficiency and fill factor (FF) was investigated, and the FF loss was analyzed. Abstract : Perovskite solar cells (PSCs) have drawn unprecedented attention due to their skyrocketing power conversion; however, their reported fill factors (FFs) still lag behind those of commercialized solar cells, and there is a lack of a comprehensive understanding of the mechanism. Here, we employed a facile and effective strategy to improve the FF to 96.3% of the Shockley–Queisser (S–Q) limit through homogeneous incorporation of CsPbBr3 crystals, which could significantly passivate deep-level hole defects, thereby leading to dramatically enhanced hole mobility to balance with electron mobility. As a result, the non-radiative recombination is suppressed along with enhanced carrier extraction efficiency, resulting in a remarkable PCE of 25.09% (certified: 24.66%) with a record FF of 86.9%, which is the highest FF among those of the reported PSCs. An in-depth analysis suggests that this strategy could concurrently reduce the FF loss caused by series resistance, shunt resistance, and non-radiative recombination. This work provides an efficient strategy to promote the FF to approach the theoretical limit.